Patient and caregiver perspectives of select non-communicable diseases in India: A scoping review. - Sindhu Nila; Eliza Dutta; S S Prakash; Sophy Korula; Anu Mary Oommen (PLoS ONE)
Background and objectives Patient-reported measures of encounters in healthcare settings and consideration of their preferences could provide valuable inputs to improve healthcare quality. Although there are increasing reports of user experiences regarding health care in India in recent times, there is a lack of evidence from Indian healthcare settings on the care provided for patients with chronic diseases. Methods We selected diabetes mellitus and cancer as representatives of two common conditions requiring different care pathways. We conducted a scoping review of studies reporting experiences or preferences of patients/caregivers for these conditions, in PubMed, Global Index Medicus and grey literature, from the year 2000 onwards. Both published and emergent themes were derived from the data and summarised as a narrative synthesis. Results Of 95 included studies (49 diabetes, 46 cancer), 73% (65) were exclusively quantitative surveys, 79% included only patients (75), and 59.5% (44) were conducted in government centres. Studies were concentrated in a few states in India, with the underrepresentation of vulnerable population groups and representative studies. There was a lack of standardised tools and comprehensive approaches for assessing experiences and preferences of patients and caregivers, concerning diabetes and cancers in India. The commonest type of care assessed was therapeutic (74), with 14 cancer studies on diagnosis and nine on palliative care. Repeated visits to crowded centres, drug refill issues, unavailability of specific services in government facilities, and expensive private care characterised diabetes care, while cancer care involved delayed diagnosis and treatment, communication, and pain management issues. Conclusions There is a need for robust approaches and standardised tools to measure responsiveness of the healthcare system to patient needs, across geographical and population subgroups in India. Health system reforms are needed to improve access to high-quality care for treatment and palliation of cancer and management of chronic diseases such as diabetes.